Tree growth and stem carbon accumulation in human-modified Amazonian forests following drought and fire - Berenguer, Erika; Malhi, Yadvinder; Brando, Paulo; Nunes Cordeiro, Amanda Cardoso; Ferreira, Joice; Franca, Filipe; Rossi, Liana Chesini [UNESP]; Moraes de Seixas, Marina Maria; Barlow, Jos (Royal Soc, 2018)
Human-modified forests are an ever-increasing feature across the Amazon Basin, but little is known about how stem growth is influenced by extreme climatic events and the resulting wildfires. Here we assess for the first time the impacts of human-driven disturbance in combination with El Nino-mediated droughts and fires on tree growth and carbon accumulation. We found that after 2.5 years of continuous measurements, there was no difference in stem carbon accumulation between undisturbed and human-modified forests. Furthermore, the extreme drought caused by the El Nino did not affect carbon accumulation rates in surviving trees. In recently burned forests, trees grew significantly more than in unburned ones, regardless of their history of previous human disturbance. Wood density was the only significant factor that helped explain the difference in growth between trees in burned and unburned forests, with low wood-density trees growing significantly more in burned sites. Our results suggest stem carbon accumulation is resistant to human disturbance and one-off extreme drought events, and it is stimulated immediately after wildfires. However, these results should be seen with caution-without accounting for carbon losses, recruitment and longer-term changes in species composition, we cannot fully understand the impacts of drought and fire in the carbon balance of human-modified forests. This article is part of a discussion meeting issue 'The impact of the 2015/2016 El Nino on the terrestrial tropical carbon cycle: patterns, mechanisms and implications'.
Keywords: drought; wildfire; tree growth; tropical forests; degradation; ENSO